Physical Therapy Interventions and Response to this Treatment in a 13-year-old Female with Paramyotonia Congenita (International Journal of Physiotherapy, 2023)
Background: Paramyotonia Congenita (PMC) is a rare genetic disorder that affects the sodium ion pump at the level of muscles, retarding muscular relaxation after activation. Symptoms may include isolated or global muscle stiffness, with or without pain. The purpose of this case is to describe physical therapy interventions and response to this treatment in a 13-year-old female with paramyotonia congenita.Case Summary: 13-year-old female diagnosed with Paramyotonia Congenita and a 4-month history of increased low back and bilateral hip pain. Treatment consisted of therapeutic heating modalities, aquatic therapy, and stretches. Patient and family education and coordination for an individual education plan were also implemented.Outcome Measures: The patient was treated at an outpatient clinic for 13 sessions. She showed improvements in shoulder, hip, and back range of motion and pain. Goniometric measurements were used to track the range of motion, and a 0-10 visual analog scale and Wong-baker FACES pain rating scale were used to measure pain.Conclusion: Physical therapy intervention may be an effective treatment option in reducing pain in a 13-year-old girl with PMC. Treatment modalities utilizing heat application may have decreased pain for several days at a time, and deeper heating options appear to yield greater effectiveness at reducing pain for longer periods. However, additional research is needed to evaluate the effectiveness of physical therapy treatment with PMC, including the role and application of deep  heat and other treatment modalities.